THU0550 New il10 receptor gene mutation associated to a spectrum of inflammatory aphthosis and crohn's disease. (12th June 2018) - Dagher, R.; Modica, V.; El Rifai, N.; Chouery, E.; Fadous Khalife, M.C.
Abstract : Background: IL-10 is defined as an anti-inflammatory cytokine. Its activity is mediated by interaction with a cell surface receptor composed of 2 subunits: alfa (IL-10RA) and beta (IL-10RB). Homozygozous mutations of IL-10RA gene have been linked to Very Early Onset Inflammatory Bowel Disease (VEO-IBD) in children with a total of 28 mutations identified till present. Objectives: We report a Lebanese family presenting with a new exonic mutation in the IL-10RA gene variably associated to inflammatory aphthosis and adult onset IBD. Methods: The proband is a boy born to consanguineous parents who presented to our attention at the age of 9. He suffered from persistent severe oral aphthosis, recurrent fever and intermittent diarrhoea since the age of 2 months, and anal aphthosis since the age of 7. His Familial history is notable for moderate oral aphthosis in the father and adult onset Crohn's disease in a paternal uncle. He was diagnosed with Behçet disease and received colchicine since the age of 8 with no efficiency. His physical exam was normal except for severe oral and anal ulcers. No history of genital ulcers. Laboratory tests revealed normal inflammatory markers. ANA titers, anti-DNA and anti-ENA were negative with normal complement level. Pathergy test and HLA B51 were negative as well as pANCA and cANCA. Iron, Zinc, vitamin and immune deficiencies were ruled out. Yearly ophthalmologic screening revealed no signs of inflammation. Repeated gastroscopy and colonoscopy and enteric MRI showed no pathologic findings. Results: A genomic sequencing study for recurrent fever was performed. A novel heterozygous exonic mutation of the IL-10RA gene (c.G172A G>A, p.E58K) was identified. The child's father and his uncle were found to have the same mutation at homozygous state, however with different phenotypic presentations. The child was started on Infliximab with favourable outcome after 3 months. Conclusions: In this Lebanese family, the previously unreported IL-10RA gene mutation (c.G172A G>A, p.E58K) is associated to a variable spectrum from benign oral aphthosis to IBD, both in homozygous and heterozygous forms. Our finding suggests that the presence of this mutation is a risk factor for inflammatory aphthosis. Whether this mutation will eventually lead to IBD is uncertain. Other unknown environnemental and genetic factors might have a role in the final phenotype of the disease. As bipolar aphthosis and recurrent fever can be misdiagnosed as Behçet disease, pro-inflammatory genetic mutations such as IL-10RA mutations should be considered in the setting of incomplete Behçet disease. References: [1] Huang Z, Peng K, Li X, Zhao R, You J, et al. Mutations in Interleukin-10 Receptor and Clinical Phenotypes in Patients with Very Early Onset Inflammatory Bowel Disease: A Chinese VEO-IBD Collaboration Group Survey. Inflamm Bowel Dis2017Apr;23(4):578–590. [2] Beser OF, Conde CD, Serwas NK, Cokugras FC, Kutlu T, et al. Clinical features of interleukin 10 receptor gene mutations in children with very early-onset inflammatory bowel disease. J Pediatr Gastroenterol Nutr2015Mar;60(3):332–8. [3] Guimarães AL, Correia-Silva Jde F, Sá AR, Victória JM, Diniz MG, et al. Investigation of functional gene polymorphisms IL-1beta, IL-6, IL-10 and TNF-alpha in individuals with recurrent aphthous stomatitis. Arch Oral Biol2007Mar;52(3):268–72. Disclosure of Interest: None declared